2019
DOI: 10.1111/desc.12896
|View full text |Cite
|
Sign up to set email alerts
|

Statistical learning of multiple speech streams: A challenge for monolingual infants

Abstract: Language acquisition depends on the ability to detect and track the distributional properties of speech. Successful acquisition also necessitates detecting changes in those properties, which can occur when the learner encounters different speakers, topics, dialects, or languages. When encountering multiple speech streams with different underlying statistics but overlapping features, how do infants keep track of the properties of each speech stream separately? In four experiments, we tested whether 8‐month‐old … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 38 publications
1
21
1
Order By: Relevance
“…This was recently replicatedwith infants by Benitez, Bulgarelli, Byers-Heinlein, Saffran, and Weiss (2019), who found that 8-monthold monolinguals were unable to learn two sequentially presented artificial languages with syllable overlap regardless of whether they were tested on the first or second language or whether the languages were differentiated by vocal pitch or speaker accent. This finding aligns with monolingual performance in the dual language task from Antovich and Graf Estes (2018).…”
Section: Research Highlightsmentioning
confidence: 73%
“…This was recently replicatedwith infants by Benitez, Bulgarelli, Byers-Heinlein, Saffran, and Weiss (2019), who found that 8-monthold monolinguals were unable to learn two sequentially presented artificial languages with syllable overlap regardless of whether they were tested on the first or second language or whether the languages were differentiated by vocal pitch or speaker accent. This finding aligns with monolingual performance in the dual language task from Antovich and Graf Estes (2018).…”
Section: Research Highlightsmentioning
confidence: 73%
“…This finding suggested that statistical learning plays an important role in language acquisition, and spurred a large body of additional work in this area, not only in developmental populations (e.g. Pelucchi et al, 2009;Fló et al, 2019;Benitez et al, 2020), but also in adults (e.g. Saffran et al, 1996b;Cunillera et al, 2009;Batterink and Paller, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have explored how speaker-specific contextual cues (e.g., two individual speakers differing in gender (Weiss et al, 2009), or accent (Benitez et al, 2020), or languages associated with two distinct faces (Mitchel & Weiss, 2010) facilitate word segmentation in two languages. However, in naturalistic bilingual environments, different speakers do not always speak distinct languages.…”
Section: Research Highlightsmentioning
confidence: 99%
“…Three recent studies have shed light on whether infants can statistically segment words from two language inputs. Benitez et al (2020) reported that 8-month-old monolingual infants failed to segment words in a dual-input segmentation task that lacked contextual cues to differentiate the two languages. In follow-up studies, they investigated whether adding distinguishing contextual cues (e.g., differences in pitch, speakers, and person-based accent) could help infants succeed.…”
mentioning
confidence: 99%